UPAYA MENGATASI PERILAKU NEGATIF ANAK USIA DINI TERHADAP PENGGUNAAN GADGET - Bahrum Amir (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The purpose of this research is to know the impact of the use of the gadget on early childhood. The type of research used in this research is qualitative research. The sampling technique used in this study using random sampling. Theoretical research is expected to add either the social sciences or sociology, especially the sociology of the family. As well as adding to the reverensi community in understanding the issues surrounding children and parents. Practically, the results of this research are expected to be learning materials and deeper knowledge about the use of gadget in children with parental controls and also add to the science and knowledge. Parents should take heart ??? in the monitor and monitor children's activity in the use of everyday gadget to minimize the negative side inflicted from the use of the gadget, gadget and should be used and exploited for anything positive. The use of gadget should not given to children under the age of 6 years, since the time of the child's age is better directed into activities which have activities surroundings for easy socializing. Keywords: Impact, Use Of Gadged, Early Childhood.